2002
DOI: 10.1182/blood-2001-12-0169
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible erythropoietin gene expression in human neuroblastoma cells

Abstract: Two human neuroblastoma (NB) cell lines, SH-SY5Y and Kelly, were found to express the gene for erythropoietin (EPO) in an oxygen (O 2 )-dependent manner. However, NB cells had maximal production of EPO with lower partial pressure of O 2 values than the well-characterized hepatoma cell line HepG2. This maximal EPO expression was preceded by accumulation of the O 2 -sensitive ␣ subunit of the heterodimeric transcription-factor complex hypoxia-inducible factor 1 (HIF-1). Western blot analysis revealed that the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 32 publications
3
72
0
Order By: Relevance
“…Recent studies have documented an important role for hypoxia in neuroblastoma cell acquisition of an immature, angiogenic, and more aggressive neural-crest-like phenotype (14,15,17). Accordingly, xenografted hypoxia-pretreated neuroblastoma cells were reported to form palpable tumors early and to grow faster than grafted normoxia-treated cells (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have documented an important role for hypoxia in neuroblastoma cell acquisition of an immature, angiogenic, and more aggressive neural-crest-like phenotype (14,15,17). Accordingly, xenografted hypoxia-pretreated neuroblastoma cells were reported to form palpable tumors early and to grow faster than grafted normoxia-treated cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 transactivates the hypoxia-responsive element (HRE) present in the promoter or enhancer elements of many genes encoding angiogenic, metabolic and metastatic factors (10,12,13), inducing their expression and contributing to the acquisition of tumor cell aggressive phenotypic changes (8 -10). Accumulation of HIF-1␣/2␣ proteins was observed in vitro in advanced-stage, metastatic human neuroblastoma cell lines exposed to hypoxia and in the hypoxic areas of experimental neuroblastoma xenografts grown in mice (14,15). Recent findings have demonstrated that hypoxia has a profound impact on neuroblastoma aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Work performed in vivo with subjects exposed to hypoxia also demonstrates an increase in expression of EPO and EPOR mRNA following reduced oxygenation (Marti, et al, 1996). Furthermore, both primary neurons , Liu, et al, 2006 and neuronal cell lines (Stolze, et al, 2002) have been found to retain the capacity to express EPO in an oxygen-dependent manner. Although EPO is recognized as a critical modulator of erythropoiesis, a low concentration of red blood cells alone does not directly stimulate EPO production, but requires the presence of a diminished oxygen tension.…”
Section: Epo Expression Structure and Receptor Role In Cells And Timentioning
confidence: 94%
“…Human Kelly neuroblastoma cells were cultured and stimulated with the HIF-inducer deferoxamine mesylate (DFX, Sigma) as reported (22), with or without recombinant human IFN-γ (HyCult Biotechnology, Uden, The Netherlands) or recombinant human TNF-α (R&D Systems, Minneapolis, MN, USA). After 24 h of incubation, EPO was measured in the supernatant by EnzymeLinked ImmunoSorbent Assay (ELISA) (Quantikine EPO, R&D Systems, sensitivity 0.6 mU/mL).…”
Section: Cell Culturementioning
confidence: 99%
“…To this end, we used Kelly human neuroblastoma cells, known to produce significant amounts of EPO protein, detectable by ELISA (22). IFN-γ or TNF, alone or in combination, did not induce EPO production in Kelly cells (not shown).…”
Section: Ifn-γ and Tnf Are Co-induced With Epo And Inhibit Its Expresmentioning
confidence: 99%